Rejestry upadłości w wybranych państwach europejskich - Janik, Ewa (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article indicates the obligations imposed on the Member States, resulting from the Regulation of the European Parliament and the Council (EU) 2015/848 of 20 May 2015 on insolvency proceedings, concerning the requirement to create at least one public register that will contain data on insolvency proceedings. In some Member States, there are already registers of bankruptcy connected with the European e-Justice Portal. In Poland, the appropriate solutions are included in the draft Act on the National Register of Debts (print no. 2367), which was created, among others, in connection with the necessity of creating the Central Register of Restructuring and Bankruptcy, referred to in art. 5 of the Act of 15 May 2015. Restructuring Law.